P2X7 receptor-mediated PARP1 activity regulates astroglial death in the rat hippocampus following status epilepticus - Kim, Ji Yang; Ko, Ah-Reum; Kim, Ji-Eun (Frontiers in Cellular Neuroscience, 2015)
Poly(ADP-ribose) polymerase-1 (PARP1) plays a regulatory role in apoptosis, necrosis, and other cellular processes after injury. Recently, we revealed that PARP1 regulates the differential neuronal/astroglial responses to pilocarpine-induced status epilepticus (SE) in the distinct brain regions. In addition, P2X7 receptor (P2X7R), an ATP-gated ion channel, activation accelerates astroglial apoptosis, while it attenuates clasmatodendrosis (lysosome-derived autophagic astroglial death). Therefore, we investigated whether P2X7R regulates regional specific astroglial PARP1 expression/activation in response to SE. In the present study, P2X7R activation exacerbates SE-induced astroglial apoptosis, while P2X7R inhibition attenuates it accompanied by increasing PARP1 activity in the molecular layer of the dentate gyrus following SE. In the CA1 region, however, P2X7R inhibition deteriorates SE-induced clasmatodendrosis via PARP1 activation following SE. Taken together, our findings suggest that P2X7R function may affect SE-induced astroglial death by regulating PARP1 activation/expression in regional-specific manner. Therefore, the selective modulation of P2X7R-mediated PARP1 functions may be a considerable strategy for controls in various types of cell deaths.